The Results of the Implantation of the Standard EN 9100 in Spanish Aerospace Sector - Prado Román, , Camilo; Castillo Peces, , Carlos del; Mercado Idoeta, , Carmelo; Soto González, , Federico (Revista Galega de Economía)
The Standards series EN 9100, is an adaptation of ISO 9000 to the specific aerospace sector, to ensure that all products related to this sector, are safe and competitive. The objectives of this study are, firstly, to analyse the results from adherence to EN 9100 by the Spanish aerospace companies, and secondly, to verify if these results are influenced by the size of these companies. With this aim a questionnaire was sent to quality manager of the 355 companies that make up this sector. Of the responses collected in the 115 questionnaires received, it is concluded that the implantation of EN 9100 has a positive influence on most of the participating companies, to obtain such benefits of both “internal" and "external", the latter of which has a higher intensity. Also, it is verifies that the size of the companies does not cause significant differences in terms of this positive influence, although in regard to small firms, the benefits of internal type, seem’s to get harder.